Detection of Branched Cracks in Beam-like Structures - TUFIȘI, Cristian (2024)
The book aims to bring contributions in the field of science and engineeringpractice, mainly in structural health monitoring by presenting methodsof identifying the position and severity of cracks in structures by usingnatural frequencies and determining the accuracy of these methods indetecting different types of damages.